2005
DOI: 10.1200/jco.2005.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Risk for Subsequent Breast Cancer After Lobular Carcinoma-In-Situ: Analysis of Surveillance, Epidemiology, and End Results Data

Abstract: LCIS is associated with increased risk of subsequent invasive disease, with equal predisposition in either breast. The minimum risk of developing IBC after LCIS is 7.1% at 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
107
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(122 citation statements)
references
References 37 publications
4
107
0
11
Order By: Relevance
“…The [9] adjusted incidence rates showed a higher risk for CBC after lobular compared to ductal carcinoma (table 3). A study of the risk of invasive cancer after lobular carcinoma in situ found an equal risk of malignancies in both breasts and a higher incidence of invasive lobular carcinoma than would be expected (Chuba et al 2005). A recent analysis of genetic predisposition to in situ and invasive lobular carcinoma of the breast found a novel lobularspecific breast cancer gene locus (Sawyer et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The [9] adjusted incidence rates showed a higher risk for CBC after lobular compared to ductal carcinoma (table 3). A study of the risk of invasive cancer after lobular carcinoma in situ found an equal risk of malignancies in both breasts and a higher incidence of invasive lobular carcinoma than would be expected (Chuba et al 2005). A recent analysis of genetic predisposition to in situ and invasive lobular carcinoma of the breast found a novel lobularspecific breast cancer gene locus (Sawyer et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that detection bias is in operation is further indicated by the high risk of ipsilateral cancer (SIR 8.06) in patients with LCIS during the first year of follow-up, as LCIS has traditionally been thought to be a marker for high risk of multifocal and contralateral disease (Frykberg et al, 1987;Page et al, 1991;Chuba et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies have shown an association between classic types and increased bilateral cancer risk, and therefore these lesions have since been regarded as a risk marker rather than a true precursor. 1,[3][4][5] Because of the recognition of indolent lesions as portending increased cancer risk, many favor the terminology of LN and LIN over the anxiety-producing word carcinoma used in the designation of LCIS (written communication with Kathleen Diehl, MD, member of The Consensus Committee of the American Society of Breast Disease, April 23, 2014). Use of the broader diagnosis of LN also reduces subjectivity related to intraobserver and interobserver variability in distinguishing ALH and LCIS.…”
mentioning
confidence: 99%